MUTUAL RECOGNITION ARRANGEMENTS (MRAS) DALAM RANGKA MASYARAKAT EKONOMI ASEAN (ASEAN ECONOMIC COMMUNITY) DALAM PERSPEKTIF HUKUM INTERNASIONAL DAN PENGARUHNYA TERHADAP HUKUM NASIONAL INDONESIA - Tony Kesuma; Sutiarnoto Sutiarnoto; Mahmul Siregar (Journal of USU International Law, 2017)
Mutual Recognition Arrangements (MRAs) in ASEAN Economic Community in the perspective of International Law and its effect in National Law. ABSTRACT   Tony Kesuma* Sutiarnoto** Mahmul Siregar***   ASEAN (Association of South East Asian Nations) is a regional organization that is composed of 10 Nations, namely Indonesia, Thailand, Malaysia, Brunei Darussalam, Lao, Cambodia, Singapore, The Phillippines, and Vietnam. ASEAN  is created to strengthen the diplomatic bond and increase the economies between member states. Because ASEAN also focuses on economy section, of course ASEAN already made quite a lot of programs to increase and generalizing the quality of human resources and chance of work, which one of their program is Mutual Recognition Arrangements (MRAs). The method author uses in this Journal is a Juridical Normative methods with category of Non Judicial Case Study, where author will explain about Mutual Recognition Arrangements (Especially in Service Sector), what MRA is in International Law, and its effects in Indonesia, especially in Legal sector. Resources in this Journal is mainly quoted from books, Law Articles, or other literatures.   The Effect of Mutual Recognition Arrangements (MRAs) in National Law is the making of Presidential Decree Number 82 Year 2002 about endorsement of ASEAN Framework on Mutual Recognition Arrangements (ASEAN MRAs), and Ministerial Regulation of Communication and Informatics Number 16 year 2012 about Guidance on the Implementation of the Recognition of a Foreign Country Test Center. There is also description about foreign worker in the professions mobilized by Mutual Recognition Arrangements in national law article, such as Article 18,19,21, and 22 of Law number 11 Year 2014 about Engineering, Article 24, 25, and 26 in Law number 38 Year 2014 about Nursery, Article 19, 20, 21, and 22 Draft Bill of Architectur, Article 7 of Ministerial Regulation of Trade number 14/M-DAG/PER/3/2006 about Provisions and procedures for Issuing a survey service business license, Article 30, 31, 32, and 50 of Law number 29 Year 2004 about Practice of medicine, Article 7 of Law Number 5 Year 2011 about Public Accountant, and Article 53 and 56 of Law number 10 Year 2009 about Tourism.